Food and nutrition security as gendered social practice - Niehof, Anke (Applied Studies in Agribusiness and Commerce, 2016)
In many parts of the world, the food security of households and the nutrition security of individual household members, in particular that of children, are still at risk, in spite of the progress made in combatting hunger at the global level. The prevailing opinion among scientists and development practioners alike is that women’s empowerment is the key to household food security and good nutrition of children. Similarly, it is thought that gender inequalities manifest themselves in dietary discrimination of women resulting in their lesser access to sufficient and nutritious food. To investigate the credibility of these ‘common truths’, empirical evidence on women’s roles in the social practices that aim at realizing household food security and good family nutrition was reviewed. It can be concluded that women definitely yield and wield power through their involvement in and responsibility for these practices, but that – at the same time – enhancing women’s capabilities by improved access to critical resources would benefit their household’s food security and their children’s nutrition. Furthermore, except for the region of South Asia, gender inequalities do not visibly result in a gender gap in nutrition, although women’s specific dietary needs in relation to pregnancy and motherhood are not always recognized.